Global macro-financial shocks and expected default frequencies in the euro area - Olli Castrén; Stéphane Dées; Fadi Zaher (European Central Bank (ECB), 2008)
Modelling the link between the global macro-financial factors and firms' default probabilities constitutes an elementary part of financial sector stress-testing frameworks. Using the Global Vector Autoregressive(GVAR) model and constructing a linking satellite equation for the firm-level Expected Default Frequencies (EDFs), we show how to analyse the euro area corporate sector probability of default under a wide range of domestic and foreign macroeconomic shocks. The results show that, at the euro area aggregate level, the median EDFs react most to shocks to the GDP, exchange rate, oil prices and equity prices. There are some intuitive variations to these results when sector-level EDFs are considered. Overall, the Satellite-GVAR model appears to be a useful tool for analysing plausible global macrofinancial shock scenarios designed for financial sector stress-testing purposes.
Keywords: C33; F47; G32; G33; 330; corporate default probability; Credit risk; Global VAR; macro stress testing; Unternehmensfinanzierung; Multinationales Unternehmen; Wirkungsanalyse; Globalisierung; Schock; Insolvenz; VAR-Modell; Theorie